المستشرق أرنولد جوزيف توينبي و آرائه حول الإسلام (دراسة تحليلية ونقدية): Orientalist Arnold Joseph Toynbee and his vision about Islam (An Analytical and Critical Study) - Dr. Muzaffar Ali (DIRAYAT, 2024)
The research titled "Orientalist Arnold Joseph Toynbee and his Vision about Islam (An Analytical and Critical Study)" delves into the influential perspective of renowned British historian and philosopher, Arnold Joseph Toynbee, on Islam. Toynbee's seminal work, "A Study of History," has profoundly shaped Western perceptions of the Muslim world. However, his portrayal of Islam as an "incomplete civilization" has sparked considerable debate and critique, particularly among scholars challenging his Orientalist lens .This paper provides an analytical and critical examination of Toynbee's Orientalist perspective on Islam and its implications within "A Study of History." By scrutinizing the historical context and philosophical underpinnings that informed Toynbee's views, the article reveals the reductionist and essentialist nature of his understanding of Islam. It argues that Toynbee's portrayal oversimplifies the complexity of Islamic civilization and fails to acknowledge its diverse contributions to human history. Through a nuanced analysis, the research article seeks to interrogate Toynbee's depiction of Islam, aiming to offer a more comprehensive understanding of the religion and its historical significance. By challenging Toynbee's Orientalist framework, the paper contributes to broader discussions surrounding the representation of Islam in Western scholarship and advocates for a more inclusive and respectful approach to studying the Muslim world.